Standard versus Endocuff versus cap‐assisted colonoscopy for adenoma detection: A randomised controlled clinical trial. Issue 4 (16th February 2021) - Floer, Martin; Tschaikowski, Laura; Schepke, Michael; Kempinski, Radoslaw; Neubauer, Katarzyna; Poniewierka, Elzbieta; Kunsch, Steffen; Ameis, Detlev; Heinzow, Hauke Sebastian; Auer, Agneta; Schmidt, Hartmut H.; Ellenrieder, Volker; et al.
Abstract: Background and aims: Adenoma detection rate (ADR) in colon cancer screening is most important for cancer prophylaxis. This work is the first three‐armed randomised controlled clinical trial aimed at comparing a head‐to‐head setting standard colonoscopy (SC) with Endocuff‐assisted colonoscopy (EC) and cap‐assisted colonoscopy (CAC) for improvement of ADR. Methods: Patients from Poland and Germany with independent indication for colonoscopy were randomised into three arms of this trial: EC, CAC and SC. Exclusion criteria were age <18 years, active Crohn's disease or ulcerative colitis, known stenosis and post‐colonic resection status. Results: A total of 585 patients (195 SC, 189 EC and 186 CAC) were enrolled in this study. Indications were not different between the groups (colorectal cancer screening 51%, diagnostic colonoscopy in 31% and post‐polypectomy follow‐up in 18%; p = 0.94). Withdrawal time was a mean of 7 min in all groups ( p = 0.658), and bowel preparation did not differ between the groups. The time to reach the caecum was significantly reduced when using the cap (a mean of 6 min for CAC vs. 7 min for SC; p = 0.0001). There was no significant difference in the primary outcome of the ADR between the groups (EC 32%, CAC 30%, SC 30%; p = 0.815). EC proved to be superior (EC vs. SC) in the sigmoid colon and transverse colon for polyp detection. Conclusion: The use of EC increased the total number of polyps seen during colonoscopy. In contrast to recent studies, no significant improvement of the ADR was detected.